EVALUASI PENGARUH KOLOM DILATASI TERHADAP KINERJA STRUKTUR PADA GEDUNG BERBENTUK LINEAR MENGGUNAKAN METODE SRPMM - PRABOWO, SINGGIH WISNU (KURVA S JURNAL MAHASISWA, 2017)
One of the methods for planning an earthquake resistant building is IntermediateMoment Resisting Frame System (IMRFS). This method is used for planning earthquakeresistant building which is used for seismic design category area.On building planning matter, dilatation system was well applied to a long span building.This dilatation system itself has a function to reduce danger of collapse building due to unequalground conditions along the building. This system also could avoid domino effect fromearthquake load that received on the building when earthquake happens. On this research writerused dilatation methods with coloum. The earthquake analysis that writer used was time historymethods, and it supported by ETABS v.9.7.2 structure analysis program. The last step wasputting out the results from completed drift.